Management of collar rot of tomato caused by Sclerotium rolfsii - Bhagat, Indramani (BIBECHANA, 2014)
Collar rot of tomato (Lycopersicum esculentum Miller) caused by Sclerotium rolfsii Sacc. is one of the most destructive diseases in tomato throughout the world. Effective and efficient management of the crop disease is generally achieved by the use of synthetic pesticides. These pesticides are known to pollute the environment, soil and water besides causing deleterious effects on human health and biosphere. Amendments (Neem cake, oil cake, cow dung, rabbit manure and chicken manure) were used in tomato seedlings to observe growth promotion and percentage increase in shoot length in healthy and treated tomato seedlings of two varieties, F1 Hybrid Arjuna and Pahuza S-22. Results revealed that growth of the tomato seedlings was significantly increased following amendment with neem cake and oil cake in the treated Sclerotium rolfsii inoculated plants than in untreated uninoculated plants as recorded. Oil cake had better effect than neem cake. Similarly, amendment with cow dung, rabbit manure and chicken manure it has been observed that the growth of tomato seedlings increased in treated uninoculated than treated inoculated tomato seedlings. Among the three treatments, cow dung gave better growth of tomato seedlings than that of rabbit manure and chicken manure. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10393 BIBECHANA 11(1) (2014) 136-140